Effect of cultivation density and methods for Betaphycus gelatinus in outdoor composite tanks: Impacts on growth and carrageenan quality - Tran , Van Huynh; Cao, Thi Thuy Hang; Vo, Thanh Trung; Truong, Anh Khoa; Tran, Mai Duc; Vu, Thi Mo; Le, Trong Nghia; Pham, Duc Thinh; Le, Truong Trung Lien; Pham, Duc Hung; Huynh, Hoang Nhu Khanh (Vietnam Journal of Marine Science and Technology, 2025)
This study evaluates the effects of stocking density and cultivation methods on the growth and quality of Betaphycus gelatinus carrageenan in a 3 m³ composite tank system. Seaweed was collected from Thai An, Ninh Thuan, Vietnam, and cultured at densities of 2, 4, 6, and 8 kg/m³ using four methods: (1) culture in hanging net cages, (2) the long-line method, (3) culture on horizontal nets and (4) cultivation attached to artificial coral. The experiment was conducted over 90 days (from June to September 2022). Results showed that the 2 kg/m³ density achieved the highest growth rate, carrageenan content, and quality (p < 0.05) compared to other densities. Among the cultivation methods, mesh cages (1) yielded the lowest growth and carrageenan quality, while the remaining three methods showed no significant differences. This study is the first report on the successful cultivation of B. gelatinus in a 3 m³ composite tank, affirming that a stocking density of 2 kg/m³ along with the hanging rope, mesh frame, and artificial coral attachment methods are optimal choices for B. gelatinus cultivation.